Exploring Non-Financial Incentives of Fresh Graduates in China from a Talent Management Perspective - Wang, Jiaying (2022)
Fresh graduates are becoming an influential component of the organization in China, so the motivation and talent management for these employees is one of the keys to the organization’s long-term development.The non-financial incentive is extensively debated and be an effective method of motivating employees. In China, however, there is a relative lack of research in this field. Therefore, this dissertation aims to explore the current situation of non-financial incentives from a talent management perspective and its importance and preferences for graduates. The dissertation referenced Herzberg's two-factor theory and undertook a qualitative research method by conducting semi-structured interviews with 22 graduates from business backgrounds.